Dynamika Powłok Lepkoplastycznych - Wierzbicki, T. (Engineering Transactions, 1971)
The approximate methods of analysis of dynamical processes in thin-walled structures are discussed in the paper. The rigid – perfectly plastic and rigid – viscoplastic models are considered. The method of linearization of the constitutive equations based upon the non-associated flow law makes it possible to determine the time-dependent profile of the shell deflection and to establish the final shape of the deformed structure. The method of estimation, on the other hand, allows for a quick determination of the maximum deflection and the response time of the structure. Both methods are illustrated by examples of solutions of a number of boundary value problems for plates and shells. The accuracy of the solutions derived is determined by comparison with the experimental data.